Peran Penyuluh Agama dalam Mengatasi Kecemasan Akan Kematian pada Lansia melalui Bimbingan Agama di Desa Hutaraja Simanungkalit - Enja Sihombing; Melina Agustina Sipahutar; Regina BM Nainggolan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the role of Christian religious instructors in addressing death anxiety in the elderly through religious guidance in Hutaraja Simanungkalit Village. Death anxiety in the elderly arises from declining physical condition, experiences of loss, a deep sense of loneliness, and an awareness of the limitations of life. In these conditions, Christian religious guidance becomes a means of spiritual support that helps the elderly cope with this anxiety. This study used a qualitative method with a descriptive approach. Data collection techniques were carried out through interviews, observation, and documentation. The research informants consisted of six people: one Christian religious instructor, one village administrator, and four elderly people. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that Christian religious instructors play a role in addressing death anxiety in the elderly through counseling techniques such as individual guidance, spiritual lectures, discussions, group prayer, and spiritual guidance. These techniques help the elderly experience changes in aspects of religious experience, understanding of faith, and worship practices, thereby reducing anxiety and gaining inner peace. The conclusion of this study confirms that Christian religious instructors have a significant contribution in helping the elderly overcome death anxiety through religious guidance that addresses cognitive, affective, and practical aspects.